Necrobacilosis in a white-tailed deer (Odocoileus virginianus peruvianus) from the Sauce Grande sector of the El Angolo Game Reserve, Piura, Peru - Elias, Roberto (2021)
The white-tailed deer (Odocoileus virginianus peruvianus) is an ungulate mammal that is widely distributed in the Peruvian coast and mountains and is one of the most exploited hunting species in the country, especially in the El Angolo Game Reserve in Piura. In 2011, hundreds of deer with signs of salivation, lameness and diarrhea were reported there, and they were finally found dead. A necropsy was done of a female found dead, samples were taken for pathology, radiology, and microbiology. Resulting in the presence of three genera of anaerobic bacteria, Fusobacterium sp., Arcanobacterium sp. and Actinomyces sp. and lesions compatible with necrobacillosis.